Commentary for dialogos (Dialogos, 2017)
The post-World War II period in Brazilian historiography is badly in need of revision. It has reflected the political currents of that era to an unhealthy degree and as a result it has produced distorted interpretations. In one dimensional fashion it portrays Getúlio Vargas as the scheming dictator who fell before the winds of democracy. And it transforms General Eúrico Dutra, who had been a mainstay of the Estado Novo, into the bearer of constitutional government. Yet curiously, at the time the Department of State in Washington worried that the “nationalist” Getúlio might return, as he did in 1951, elected as the paladin of the people. The immediate post-war years set the patterns of politics, economic development, military and foreign relations down to 1964.